Interspecific competition between Mastrus ridens and Liotryphon caudatus ectoparasitoids of codling moth Cydia pomonella - Sandanayaka, W.R.M.; Davis, V.A.; Charles, J.G. (New Zealand Plant Protection, 2016)
Mastrus ridens is a gregarious ectoparasitoid and Liotryphon caudatus is a solitary ectoparasitoid of cocooned codling moth larvae These two parasitoid species could potentially compete for resources because they oviposit and develop on the same lifestage of their host Competition experiments in the laboratory showed that females of both species oviposited into host cocoons regardless of previous parasitism but adults of only one species ever emerged Liotryphon caudatus larvae were highly aggressive They preyed upon eggs and larvae of M ridens as well as conspecifics such that only a single adult L caudatus emerged Mastrus ridens larvae survived competition with L caudatus if they had a sufficient time to develop to a size that could attack L caudatus eggs However L caudatus was often still able to outcompete M ridens even when M ridens eggs were laid first Mastrus ridens hyperparasitised L caudatus larvae that had themselves cocooned within the host cocoon but no parasitoids emerged Liotryphon caudatus outcompeted M ridens in an enclosed space but that ability in a natural ecosystem remains to be investigated